ASSISTANCE FOR REGISTRATION BRAND OF LAUNDRY COST AS PROTECTION EFFORT ON INTELLECTUAL PROPERTY - Jeslin Jeslin; Hari Sutra Disemadi (Universitas Internasional Batam, 2022)
In making a brand, it must have a different characteristic from the other so the product that listed will be easier to recognize. From the results of observation, that LAUNDRY COST is one of the Micro, Small and Medium Enterprises (MSME) in Tanjungpinang city that haven’t registered the brand. So this community services (PkM) is for provide a legal protection of brand rights from the country for the applicant. There are 3 method for this implementation, such as: pre implementation, implementation stage, and the last stage is evaluation. The result of this community services (PkM) is that business owner know about the risk of not registering the brand and the importance of brand protection. MSME actors also get a receipt for the registration brand of LAUNDRY COST from DJKI website.